Set‐up error and dosimetric analysis of HexaPOD evo RT 6D couch combined with cone beam CT image‐guided intensity‐modulated radiotherapy for primary malignant tumor of the cervical spine. Issue 4 (14th March 2020) - Jiang, Ping; Zhang, Xile; Wei, Shuhua; Zhao, Tiandi; Wang, Junjie
Abstract: Purpose: To investigate the set‐up error and consequent dosimetric change in HexaPOD evo RT 6D couch under image‐guided intensity‐modulated radiotherapy (IG‐IMRT) for primary malignant tumor of the cervical spine. Methods: Ten cases with primary malignant tumor of the cervical spine were treated with intensity‐modulated radiotherapy (IMRT) in our hospital from August 2013 to November 2014. The X‐ray volumetric images (XVI) were scanned and obtained by cone‐beam CT (CBCT). The six directions (6D) of set‐up errors of translation and rotation were obtained by planned CT image registration. HexaPOD evo RT 6D couch made online correction of the set‐up error, and then the CBCT was conducted to obtain the residual error. Results: We performed set‐up error and dosimetric analysis. First, for the set‐up error analysis, the average error in three translation directions of 6D set‐up error of the primary tumor of the cervical spine was <2 mm, whereas the single maximum error (absolute value) is 7.0 mm. Among average errors of rotation direction, Rotation X (RX) direction 0.67° ± 0.04°, Rotation Y (RY) direction 1.06° ± 0.06°, Rotation Z (RZ) direction 0.78° ± 0.05°; and the single maximum error in three rotation directions were 2.8°, 3.8°, and 2.9°, respectively. On three directions (X, Y, Z axis), the extended distance from clinical target volume (CTV) to planning target volume (PTV) was 3.45, 3.17, and 3.90 mm by calculating, respectively. Then, for the dosimetric analysis, the parameters, including plan sum PTV D98 and D95, planning gross tumor volume D98 and D95, V100% of the plan sum were significantly lower than the treatment plan. Moreover, Dmax of the spinal cord was significantly higher than the treatment plan. Conclusion: 6D set‐up error correction system should be used for accurate position calibration of precise radiotherapy for patients with malignant tumor of the cervical spine.